Karakteristik Dinamis Pegas Udara - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian UGM, 2005)
ABSTRAK An air spring is a system that has a spring and inherent damping behavior so that it can be used as vibration isolator or shock absorber. Objective of this research is to investigate dynamic characteristic of an air spring. This research developes a research conducted by Jayatun (2003), in which the bellows used is expansion joint whereas the air pressure used are 80 psig until 0 psig that varied with interval 5 psi. The research is conducted for two vibration modes that are vertical mode (lateral mode) and bending mode (transversal mode). The both modes are examined at transient and steady state conditions. The result of the transient examination shows that for the various of air pressure used so in the both modes are obtained constant of spring (k) and natural frequency (fp) that are inclined decrease as increasing of Mass Pressure Ratio (MPR) value whereas damping ratio R) is inclined increase. On the other hand, the result of the steady examination shows that the good performance will be achieved by the air spring which is used as vibration isolator in lateral mode as long as the recommended working frequency, fp < 25 Hz or fp > 60 Hz whereas 20 Hz < fp < 50 Hz in transversal mode. The system should be added an equipment to improve its damping ratio when the air spring to be used as shock absorber. That is recommended because the air spring has low value of damping ratio in the both lateral and transversal modes. Keywords: desulfurasi, deashing batubara